Laser-based 3D printing using bessel beams for tissue engineering applications - Liew, Andy Wen Loong (Nanyang Technological University, 2020)
The ultimate goal of tissue engineering and regenerative medicine is the successful fabrication of functional tissue in the lab for implantation into patients to treat damaged tissue and organs. Over the years, 3D printing technology has emerged as a promising technique to achieve this goal as it offers superior control over construct architecture and cell placement. Scientists today are continually seeking to improve the technology in order to produce more complex biofunctional tissue constructs which eludes the tissue engineering community to this day. Scientists are also faced with the challenge of implant pre-vascularization which is deemed essential for long- term efficacy of the tissue construct post-implantation. This has led to the development of a variety of vascularization techniques in recent years. In this dissertation, a laser-based 3D printing technique using Bessel Beams was studied for applications in tissue engineering. Compared to conventional fabrication techniques, the Bessel Beam (BB) printing technique demonstrated unique advantages which includes easily customizable construct architecture, reduced fabrication time, high print resolution, and the ability to print high aspect ratio tubular structures with anatomical relevance without the need for support material. Through the characterization of endothelial cells encapsulated within hydrogel matrix, It was found that while collagen gel was capable of supporting cell viability and inducing endothelial sprouting, these self-assembled endothelial networks were only found on the 2D substrate surface and not within the 3D gel matrix. These networks were also found to be non-lumenized, which contradicts some reports found in the literature. It was also found that encapsulation of endothelial cells within spatially confined collagen gels is necessary for self-assembled endothelial cord formation. These results laid the foundation for subsequent cell printing experiments. Live endothelial cells were then successfully encapsulated within hydrogel fibers using the BB printing technique and shown to possess superior cytocompatibility compared to conventional extrusion and inkjet-based printing systems. High resolution fibers down to 25 μm were printable using the BB technique, a significant improvement compared to conventional microfluidics and wet spinning techniques, and the capability to tune the fabricated fiber diameter based on mathematical models was also demonstrated. Finally, endothelial cells encapsulated within cell-laden hydrogel fibers were shown to self-assemble into endothelial cords in vitro which is desirable for pre-vascularization applications. Overall, the work presented in this dissertation solidifies the BB printing technique as a promising fabrication approach with significant applications in tissue engineering, particularly in the field of the vascularization of tissue constructs.